Intermodal Transport Market a Pandemic Situation In 2019-2020 - Szymon MACHAŁA; Norbert CHAMIER-GLISZCZYNSKI (Communications of International Proceedings, 2021)
The article presents the impact of the pandemic situation on the intermodal transport market in Poland in 2019-2020. The aim of this article is to demonstrate the direct impact of pandemic factors on the development of intermodal transport. Both service providers operating in the market of intermodal services and the development of intermodal terminals located in Poland will be taken into consideration. This raises the question of whether the pandemic situation has translated directly into the number of service providers, the number of active inland intermodal terminals and transport performance. Figures and statistics were obtained from the Central Statistical Office and the Railway Transport Office.
Keywords: Pandemic; Market; Terminal; Intermodal Transport